Away inside: emigrants and transnationalism through the eyes of political parties - Abrantes, M. (2017)
This article examines how political parties in Portugal organize concerning emigrants and the subject of migration outflow, uncovering the issues and strategies that they favour. The 2009 Portuguese legislative elections offer a privileged site for empirical inquiry. Not only are emigrants able to elect members of the national parliament through particular voting districts, but also a complete period of electoral campaigning under standard institutional conditions (rather than early elections) could thus be followed in real-time by the research team. Analysis draws chiefly on electoral manifestos, campaign activities, and first-hand interviews with members of the parliament and public officials. A close tie between the capacity of parties to organize abroad and the salience of issues related to the emigrant population in party programs is exposed. It is argued that the ambiguous position of external voting between the strengthening of national(istic) bonds and transnational citizenship is disputed within the party system, since attitudes towards each of these perspectives vary across parties. Parties must therefore be understood as key players in the ongoing redefinition of the political agency of migrants, bearing a significant impact on their participation and representation. Last, implications for future research are addressed.